Multisensory integration across the menstrual cycle - Ocklenburg, Sebastian; Wolf, Claudia C.; Heed, Tobias; Ball, Anna; Cramer, Holger; Röder, Brigitte; Güntürkün, Onur (Frontiers in Psychology, 2013)
Evidence suggests that spatial processing changes across time in naturally cycling women, which is likely due to neuromodulatory effects of steroid hormones. Yet, it is unknown whether crossmodal spatial processes depend on steroid hormones as well. In the present experiment, the crossmodal congruency task was used to assess visuo-tactile interactions in naturally cycling women, women using hormonal contraceptives and men. Participants adopted either a crossed or uncrossed hands posture. It was tested whether a postural effect of hand crossing on multisensory interactions in the crossmodal congruency task is modulated by women's cycle phase. We found that visuotactile interactions changed according to cycle phase. Naturally cycling women showed a significant difference between the menstrual and the luteal phase for crossed, but not for uncrossed hands postures. The two control groups showed no test sessions effects. Regression analysis revealed a positive relation between estradiol levels and the size of crossmodal congruency effects, indicating that estradiol seems to have a neuromodulatory effect on posture processing.